Teaching about Islam in Africa: A Cultural-Functional Perspective (American Journal of Islam and Society, 2014)
What are the major pillars of education today? The International Commission on Education for the Twenty-first Century focused on this question in its report to the premier United Nations agency in education: the United Nations Educational, Scientific and Cultural Organization (UNESCO). In its report, “Learning: The Treasure Within,” the commission stated that life-long education is based upon four pillars: learning to know, learning to do, learning to live together, and learning to be.1 But is learning about religion a steel bar in these pillars? Certainly, the High-Level Group (HLG) appointed by Kofi Annan, the African UN Secretary General (1997-2006), to undertake the major UN intercultural initiative – the UN Alliance of Civilizations (UNAOC) – seemed to think so. The HLG report stressed the role of learning about religion as a key element of preparing future citizens for a world characterized by cultural diversity.What are the major pillars of education today? The International Commission on Education for the Twenty-first Century focused on this question in its report to the premier United Nations agency in education: the United Nations Educational, Scientific and Cultural Organization (UNESCO). In its report, “Learning: The Treasure Within,” the commission stated that life-long education is based upon four pillars: learning to know, learning to do, learning to live together, and learning to be.1 But is learning about religion a steel bar in these pillars? Certainly, the High-Level Group (HLG) appointed by Kofi Annan, the African UN Secretary General (1997-2006), to undertake the major UN intercultural initiative – the UN Alliance of Civilizations (UNAOC) – seemed to think so. The HLG report stressed the role of learning about religion as a key element of preparing future citizens for a world characterized by cultural diversity.2 In his Cultural Forces in World Politics(1990), Ali Mazrui explored the seven functions of culture in society. Briefly put, these are culture as a worldview, a source of identity, stratification, communication, value systems, motivation, and as a means of production and modes of consumption. I apply this framework to my analysis of the seven functions of Islam in Africa and link them with the UNESCO and UNAOC reports to underline the need for modern well-educated Africans to learn about Islam in Africa. In his Cultural Forces in World Politics(1990), Ali Mazrui explored the seven functions of culture in society. Briefly put, these are culture as a worldview, a source of identity, stratification, communication, value systems, motivation, and as a means of production and modes of consumption. I apply this framework to my analysis of the seven functions of Islam in Africa and link them with the UNESCO and UNAOC reports to underline the need for modern well-educated Africans to learn about Islam in Africa.